2010
DOI: 10.1523/jneurosci.1125-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Mental Retardation Protein Is Required for Rapid Experience-Dependent Regulation of the Potassium Channel Kv3.1b

Abstract: Fragile X Mental Retardation Protein (FMRP) is an RNA-binding protein that regulates synaptic plasticity by repressing translation of specific mRNAs. We found that FMRP binds mRNA encoding the voltage-gated potassium channel Kv3.1b in brainstem synaptosomes. To explore the regulation of Kv3.1b by FMRP, we investigated Kv3.1b immunoreactivity and potassium currents in the auditory brainstem sound localization circuit of male mice. The unique features of this circuit allowed us to control neuronal activity in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 57 publications
6
147
0
1
Order By: Relevance
“…It has been reported that FMRP directly binds to KCNC1 mRNA 43 . DISC1 and FMRP may cooperatively regulate the localization and translation of Kcnc1 mRNA for synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FMRP directly binds to KCNC1 mRNA 43 . DISC1 and FMRP may cooperatively regulate the localization and translation of Kcnc1 mRNA for synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro screening assays have identified several voltage-gated potassium, sodium, and calcium channels as potential FMRP mRNA targets [44,67,100,101]. Two of them, the voltage-gated potassium channels Kv3.1b and Kv4.2, were validated in independent studies as FMRP mRNA targets [74,102,103]. While Kv3.1b was shown to be translationally repressed by FMRP, the exact modalities of FMRP-mediated regulation of Kv4.2 are not fully understood yet, and it is still controversial if FMRP acts as a translational suppressor or activator of Kv4.2 [74,103].…”
Section: Fmr1mentioning
confidence: 99%
“…In vitro screens have suggested that FMRP might associate with up to 4% of all mRNAs present in the brain Miyashiro et al, 2003), and the identified mRNA targets encode proteins important for various cellular mechanisms, such as cytoskeletal regulation, AMPA receptor trafficking, synaptic structure and composition, and synaptic signal transmission (Zalfa et al, 2003;Lu et al, 2004;Muddashetty et al, 2007;Schutt et al, 2009;Strumbos et al, 2010). FMRP is not only a multifaceted regulator of numerous target mRNAs, but is also itself activity-regulated at multiple steps, such as FMRP synthesis at synapses (Weiler et al, 1997), protein and mRNA localization in dendrites and at synapses (Antar et al, 2004), and posttranslational modifications and protein stability (reviewed in Bassell and Warren, 2008;De Rubeis and Bagni, 2010;Pfeiffer and Huber, 2009).…”
Section: Fmrp: a Key Regulator Of Neuronal Functionmentioning
confidence: 99%